2015
DOI: 10.1016/j.micres.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Melanin is required for the formation of the multi-cellular conidia in the endophytic fungus Pestalotiopsis microspora

Abstract: Melanin plays an important role in regulating various biological processes in many fungi. However, its biological role in conidiation remains largely elusive. We report here that conidia production, morphogenesis, integrity, germination and their viability in Pestalotiopsis microspora require the polyketide-derived melanin. A polyketide synthase gene, pks1, was identified and demonstrated responsible for melanin biosynthesis in this fungus. A targeted deletion mutant strain Δpks1 displayed a defect in pigmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 40 publications
3
54
0
2
Order By: Relevance
“…S3) and LC‐MS (data not shown) but no difference in metabolites was identified. The same situation also happened in the disruptions of MrPKS1 in M. robertsii (Chen et al ., ), PKS12 and PKS13 in B. cinerea (Schumacher, ) as well as PKS1 in P. microspora (Yu et al ., ). All of these PKS are involved in the pigment formation but no identified compounds were found.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S3) and LC‐MS (data not shown) but no difference in metabolites was identified. The same situation also happened in the disruptions of MrPKS1 in M. robertsii (Chen et al ., ), PKS12 and PKS13 in B. cinerea (Schumacher, ) as well as PKS1 in P. microspora (Yu et al ., ). All of these PKS are involved in the pigment formation but no identified compounds were found.…”
Section: Discussionmentioning
confidence: 99%
“…Searching the genome for pigment biosynthetic genes in P. fici genome, we found a putative PKS with considerable homology to other melanin encoding enzymes. Deletion of the PKS encoding gene PfmaE led to colorless conidia and serious fractures on conidial surfaces in P. fici which is consistent with the deletion of pks1 in P. microspora (Yu et al ., ). As different extraction methods and analyses by HPLC and LC‐MS analysis could not distinguish chemical differences between WT and the PfmaE mutant, we explored an alternative approach to address this problem.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for this is still unknown. In fungi, many PKS genes encoding the melanin biosynthesis have been cloned and characterized Loppnau et al 2004;Eisenman and Casadevall 2012;Yu et al 2015). It has been reported that the transcriptional activators Gat1, Gln3 and AreA and the transcriptional repressors Deh1, Dal80 and AreB are involved in nitrogen repression in fungi (Rød-kaer and Faergeman 2014).…”
Section: Expression Of the Pks Gene In Different Yeast Strainsmentioning
confidence: 99%
“…6). Melanin in the conidia of an endophytic fungus P. microspora also plays an important role in resistance to the oxidative stress of H 2 O 2 (Yu et al 2015). The melanized cells of a wild-type Sporothrix schenckii were less susceptible to killing by a chemically generated oxygen from H 2 O 2 than its non-melanized cells (Romero-Martinez et al 2000).…”
Section: Resistance To High Oxidationmentioning
confidence: 99%